INVESTIGATION OF FATTY ACID’S COMBINATION IN HERBAL COMPOSITION WITH NEUROPROTECTIVE EFFECT - T. A. Turtuyeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The study of chemical composition of lipophilic fraction is carried out. The presence of saturated (palmitic, stearic, arachinic) and unsaturated, irreplaceable (linoleic, linolenic) fatty acids has been established.